Monitorización y efectos secundarios de los inmunosupresores en el trasplante - Llancaqueo V. , Marcelo (Revista Hospital Clínico Universidad de Chile, 2007)
The success of organ transplants and their consideration as a clearly established treatment in some indications is due to the development of immunosuppressant drugs. While it was not the first of the drugs to be employed, the introduction of cyclosporin in the 1980s in immunosuppressant treatment made possible an increase in the number of transplants and the success of this practice. From then onwards, immunosuppression has been based on the use of a combination of drugs, initially cyclosporin, corticoids and azathioprine. In recent years new drugs have been introduced that have opened up the possibilities of treatment. But many pending questions remain, due to the toxicity associated with their use and the possibility of interaction with other drugs, which complicates their use and can compromise the prognoses of these patients. Calcineurin inhibitors and mTOR are the drugs involved with greater frequency in interactions with other drugs, which makes it necessary to anticipate this possibility when the concomitant medication is changed.